Tribal art - Geoffroy-Schneiter, Berenice (Talk about, 2013)
From cave painting to aboriginal body art--the first tattoos--and from statues to masks, this volume covers the spectrum of tribal art and sets misconceptions straight. Gauguin, Picasso, and Giacometti were inspired by it--but what exactly is tribal art? Exposing old clichâes and outdated ideas, this clearly written and vividly illustrated volume explains the art form's key concepts--from the basics of material and form, to underlying beliefs--and takes the reader through its history, geography, and techniques, from the bright blue statues of the Solomon Islands to pre-Colombian abstract feather artwork. A section on the artists and movements inspired by tribal art attests to its lasting influence, while an illustrated list of the world's thirty most significant works of tribal art allows the reader to discover their impact firsthand. A glossary of terms, a list of where to see tribal art, and a chronology of major ethnological expeditions and exhibitions complete this indispensable guide to the world's oldest art"--Amazon.com, viewed July 1, 2013.